Rethinking energy demand governance: Exploring impact beyond 'energy' policy. (February 2018) - Butler, C.; Parkhill, K.A.; Luzecka, P.
Abstract: The challenges of climate change and energy security, along with problems of fuel poverty and energy justice bring imperatives to create transitions in energy demand. Academic research and theory have begun to highlight the ways that government policies, strategies, and processes across wide-ranging areas of policy, from health to work and the economy, shape everyday practices with significant implications for energy demand. This brings focus on the role of governance in shaping energy demand far beyond what might traditionally be characterised as 'energy' policy. Situating these ideas in terms of relational geographical concepts of governance, this paper analyses qualitative interview data with actors involved in governing along with documentary material, to highlight four different ways in which non-energy related governance can have important implications for energy issues. The central contribution of the paper is to set out a distinctive analytic framework for making visible 'non-energy' policy impacts, which might otherwise be obscured within analysis. The article concludes reflecting on the implications of the analysis for rethinking the governance of energy demand to meet contemporary challenges.